Pengaruh Motivasi dan Komitmen Terhadap Kinerja Kader Surabaya Hebat Pada Kegiatan Posyandu di Wilayah Kerja Kelurahan Tembok Dukuh Kecamatan Bubutan Kota Surabaya - Ananta, Yogeshwara Pramudya; Eprilianto, Deby Febriyan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The performance of the Kader Surabaya Hebat essentially represents the outcomes achieved by one of the government programs in supporting the delivery of public health services, particularly through Posyandu (Intregrated Service Post) activities. However, the implementation of these activities still faces various challenges, such as the absence of cadres and a lack of motivation and commitment in carrying out their duties. This study aims to analyze and evaluate the impact of motivation and commitment on the performance of Kader Surabaya Hebat in Posyandu activities in the working area of Tembok Dukuh Urban Village Bubutan District Surabaya City. The research was conducted by distributing questionnaires to 90 respondents, with the study population consisting of all 281 active Kader Surabaya Hebat in Tembok Dukuh Urban Village, representing 10 neighborhood associations (RW) in the area. The study examines the independent variables (motivation and commitment) in relation to the dependent variable (performance). The method used in this research is quantitative descriptive, and data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 4 software. The results of the study show that motivation has a positive effect on cadres performance at a rate of 0.220, indicating that higher motivation levels lead to more optimal performance. Moreover, commitment has a more significant effect on cadres performance, with a rate of 0.496. The variables of motivation and commitment simultaneously show an impact on performance with a value of 0.714, indicating an effect of 71.4%. This is also supported by the path coefficient results of motivation and commitment on performance, with a t-statistic value ≥ 1.96 and a p-value ≤ 0.05. These findings emphasize that enhancing the motivation and commitment of cadres can be a key factor in optimizing the delivery of community health services at the urban village level.